Understanding Religious Moderation Literacy in Students at SMP Negeri 5 Sentani - GodlifMalatuny, Yakob; Warwer, Fredrik; W. Pentury, Jolanti; Labobar, Julianus; FManuri, Engel (Abdi Masyarakat, 2024)
Understanding religious moderation literacy at SMP Negeri 5 Sentani is an urgent need to anticipate future social challenges. In order to answer this need, a team of lecturers from the STAKPN Sentani Christian Religious Education Department held community service activities with the main aim of increasing understanding of religious moderation literacy among students. This activity proved to be very relevant and effective in addressing the issue of religious moderation in the school. The PkM team succeeded in delivering material regarding the challenges of practicing religious moderation, the role of education in advancing moderation, as well as strategies for increasing religious moderation literacy in a way that was easy for students to understand. As a result, this activity had a significant positive impact on increasing knowledge of religious moderation literacy for students at SMP Negeri 5 Sentani.